Crossover in the inelastic electron tunneling spectra of conjugated molecules with direct Au–C links. Issue 3 (8th January 2019) - Montes, Enrique; Foti, Giuseppe; Vázquez, Héctor
Abstract : We use inelastic electron tunneling spectroscopy (IETS) first-principles simulations to identify and characterize the different vibrational modes of single conjugated molecules bonded to Au metal electrodes. Abstract : We use inelastic electron tunneling spectroscopy (IETS) first-principles simulations to identify and characterize the different vibrational modes of single conjugated molecules bonded to Au metal electrodes. The molecules are polyphenyls (with 1 to 4 benzene units) bonded to Au via highly conducting direct Au–C bonds. The short molecule shows near resonant elastic transmission, with a crossover to tunneling for the longer backbones. The calculated inelastic spectra exhibit dips in the IETS signal of the short molecule and peaks for the longer molecules. We characterize the symmetry of vibrational modes and scattering states and discuss the changes with increasing length, where the inelastic signal of different modes can be amplified, quenched or present a crossover as more benzene units are added to the molecular backbone. This analysis rationalizes the observed trends as a function of molecular length and illustrates the role of electronic and vibrational properties on Au–C bonded molecular junctions.